Analysis of beta-cell maturity and mitochondrial morphology in juvenile non-human primates exposed to maternal Western-style diet during development - Carroll, Darian T.; Miller, Allie; Fuhr, Jennifer; Elsakr, Joseph M.; Ricciardi, Valerie; Del Bene, Alexa N.; Stephens, Stedman; Krystofiak, Evan; Lindsley, Sarah R.; Kirigiti, Melissa; Takahashi, Diana L.; Dean, Tyler A.; et al. (Frontiers in Endocrinology, 2024)
Introduction: Using a non-human primate (NHP) model of maternal Western-style diet (mWSD) feeding during pregnancy and lactation, we previously reported altered offspring beta:alpha cell ratio in vivo and insulin hyper-secretion ex vivo. Mitochondria are known to maintain beta-cell function by producing ATP for insulin secretion. In response to nutrient stress, the mitochondrial network within beta cells undergoes morphological changes to maintain respiration and metabolic adaptability. Given that mitochondrial dynamics have also been associated with cellular fate transitions, we assessed whether mWSD exposure was associated with changes in markers of beta-cell maturity and/or mitochondrial morphology that might explain the offspring islet phenotype. Methods: We evaluated the expression of beta-cell identity/maturity markers (NKX6.1, MAFB, UCN3) via florescence microscopy in islets of Japanese macaque pre-adolescent (1 year old) and peri-adolescent (3-year-old) offspring born to dams fed either a control diet or WSD during pregnancy and lactation and weaned onto WSD. Mitochondrial morphology in NHP offspring beta cells was analyzed in 2D by transmission electron microscopy and in 3D using super resolution microscopy to deconvolve the beta-cell mitochondrial network. Results: Analysis of beta-cell maturity markers in islets of NHP offspring from WSD-fed dams, showed no differences when compared to offspring from dams fed a control diet, at 1 or 3 years of age. Regardless of maternal diet, the beta-cell mitochondrial network was found to be primarily short and fragmented at both ages in NHP; overall mitochondrial volume increased with age. In utero and lactational exposure to maternal WSD consumption had no effect on these parameters. Discussion: Despite mWSD consumption having clear developmental effects on offspring beta:alpha cell ratio and insulin secretory response to glucose, this does not appear to be mediated by changes to beta-cell maturity or the beta-cell mitochondrial network. In general, the more fragmented mitochondrial network in NHP beta cells suggests greater ability for metabolic flexibility.